Writing Vietnam, writing life : Caputo, Heinemann, O'Brien, Butler - Herzog, Tobey C. (University of Iowa Press, 2008)
"Philip Caputo, Larry Heinemann, Tim O'Brien, and Robert Olen Butler: four young midwestern Americans coming of age during the 1960s who faced a difficult personal decision - whether or not to fight in Vietnam. Each chose to participate. After coming home, these four veterans became prizewinning authors telling the war stories and life stories of soldiers and civilians. The four extended conversations included in Writing Vietnam, Writing Life feature revealing personal stories alongside candid assessments of each author's distinct roles as son, soldier, writer, and teacher of creative writing." "As Tobey Herzog's thoughtful interviews reveal, these soldier-authors have diverse upbringings, values, interests, writing careers, life experiences, and literary voices. They hold wide-ranging views on, among other things, fatherhood, war, the military, religion, the creative process, the current state of the world, and the nature of both physical and moral courage. For each author, the conversation and richly annotated chronology provide an overview of the writer's life, the intersection of memory and imagination in his writing, and the path of his literary career. Together, these four life stories also offer mini-tableaux of the fascinating and troubling time of 1960s and 1970s America. Above all, the conversations reveal that each author is linked forever to the Vietnam War, the country of Vietnam, and its people."--Jacket.